PENGARUH MODEL PEMBELAJARAN NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIKA - Mirasia; Ade Susanti; Awatif (Matedukasia, 2024)
This research aims to determine whether there is an influence of the NHT Learning Model on the Learning Outcomes of Class IX MTS Negeri 1 Merangin Students for the 2023/2024 Academic Year. This research uses quantitative research using the True Experimental Design method, namely Posttest-Only Control Design. The population in the study were all students of Class IX MTS N 1 Merangin for the 2023/2024 academic year, consisting of 6 classes. The sampling technique uses simple random sampling. The data analysis technique used to test the hypothesis is the t-test. The research results show that the use of the NHT model has a significant impact on student learning outcomes compared to conventional methods. Where the results of the t-test show that the tcount value is 3.296 > the ttable value of 1.671. This means that there is a significant difference in learning outcomes between the experimental group and the control group. So, it can be concluded that in the context of this research, the use of the NHT type cooperative model has a significantly positive effect on student learning outcomes in mathematics subjects. This model can be considered an effective learning approach to improve students' understanding and achievement in the subject.